Meeting Questions: a New Season (2013)
These are the questions posed by participating children of the EAFIT Children's University that inspire the workshops of the 2013-2014 season of Encounters with the Question, first stage of the program: Why do mathematics exist? How does a ship float, how does a robot work?, Why is there science?, Why are we afraid,, Why were coins and banknotes invented?